Multi-scale approach to non-adiabatic charge transport in high-mobility organic semiconductors - Heck, Alexander; Kranz, Julian; Kubař, Tomáš; Elstner, Marcus (Journal of chemical theory and computation, 2015)
A linear scaling QM/MM model for studying charge transport in high-mobility molecular semiconductors is presented and applied to an anthracene single crystal and a hexabenzocoronene derivative in its liquid crystalline phase. The model includes both intra- and intermolecular electron-phonon couplings, long-range interactions with the environment, and corrections to the self-interaction error of density functional theory. By performing Ehrenfest simulations of the cationic system, hole mobilities are derived and compared to the experiment. A detailed picture of the charge carrier dynamics is given, and the performance of our method is discussed.